Landslide Type Prediction using Random Forest Classifier - NG, Harish Kumar; G, Pooventhiran; D, Karthika Renuka (International Journal of Computer Sciences and Engineering, 2020)
This paper talks about the prediction of types of landslides. It employs Random Forest Classifier technique, the ensemble version of Decision Trees. The results of the experiment show that ensemble techniques provide a better result compared to other algorithms. The dataset used here, in this paper, is Landslides After Rainfall dataset from NASA. This model achieves 59% accuracy without feature selection and 84% accuracy with feature selection.